Comparative Analysis of Chinese and US New Energy Vehicle Markets and Development Strategies of Chinese New Energy Enterprises - Nie, Xinyan (Transactions on Economics, Business and Management Research, 2024)
This study conducts a comprehensive analysis of the electric vehicle (EV) industries in China and the United States, recognizing their pivotal role in global economic growth, environmental sustainability, and energy security. With the EV market experiencing rapid expansion driven by government support and consumer demand for eco-friendly products, this paper underscores the importance of exploring the strategies of these two markets. By examining market dynamics, technological innovations, and policy frameworks in both countries, the study reveals similarities and differences in their approaches. While China’s growth is largely policy-induced, the US market is primarily market-driven. The paper offers strategic recommendations to capitalize on strengths and address weaknesses, emphasizing the need for cross-country cooperation on infrastructure, consumer education, and technical and regulatory standards. Recognizing the significant impact of national strategies on global EV industry competitiveness, the study emphasizes the importance of understanding these factors for fostering sustainable growth and innovation. Future research should incorporate primary data to delve deeper into consumer behavior and refine market forecasts, ensuring continued insights into the sector’s development.